Political Effects on the Allocation of Public Expenditures: Empirical Evidence from OECD Countries - Niklas Potrafke (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
This paper examines the effects of political determinants on the allocation of public expenditures. Analyzing an OECD panel from 1990 to 2004, a SURE model controls for the contemporaneous correlation between the different expenditure categories (COFOG). I find that left governments set other priorities than right governments: In particular, they increase spending for ?Environment protection?, ?Recreation; Culture and Religion? and ?Education?. The number of coalition partners as well as minority governments affects the allocation of public expenditures, too. In contrast, there are no election and pre-election year effects.
Keywords: D72; H50; E62; 330; allocation of public expenditures; partisan politics